Developing a robotics-based advocacy framework for electronics engineering using an integrated KANO–IPA–QFD approach - Helen Grace Gonzales; Alenogines L. San Diego; Consorcio Namoco (Innovation in Engineering, 2026)
Electronics Engineering (ECE) remains strategically important to national technological capability and workforce development in the Philippines, yet student interest in the field is often weak and insufficiently structured. Although educational robotics has been widely associated with positive STEM-related outcomes, fewer studies have examined robotics as a discipline-specific advocacy strategy, and even fewer have translated student-valued robotics attributes into a structured framework for promoting a specific engineering discipline. Addressing this gap, this study developed a Robotics-Based Advocacy Framework for Electronics Engineering using an integrated KANO Model, Importance Performance Analysis (IPA), Quality Function Deployment (QFD) approach within a multiphase mixed-method framework development design. In Phase 1, 25 robotics learning attributes were analyzed. KANO results identified three Attractive attributes, hands-on robot building, sensor integration, and confidence-building tasks, while Better–Worse analysis showed the highest satisfaction gains for affordable robotics kits (56.19%), sensor integration (55.56%), and hands-on robot building (55.14%), with the strongest dissatisfaction risk found in clear learning modules and tutorials (-23.36%). IPA showed that 14 attributes were located in Quadrant I, while only community-centered robotics (F22) fell in Quadrant II, marking it as the primary enhancement area. QFD ranked Experiential Robotics Ecosystem first (64.5422; 22.32%), followed by Structured Curriculum Framework (54.9790; 19.02%), Faculty Development (31.5294; 10.91%), and Mentorship and Industry Linkages (30.0270; 10.39%). In Phase 2, pilot results showed positive mean gains across five domains, with the overall mean increasing from 3.02 to 3.44. The study produced a theory-informed, learner-centered, and data-driven advocacy framework, with pilot findings providing preliminary support for its practical relevance.